Applied Ergonomic Design Of E-Bike With Antropometric Approach - Iqbal Trio Pambud; M. Nushron Ali Mukhtar; Ayu Dwi Candra Kartika (Tibuana, 2022)
Transportation is a tool that can be easiness for mobilities a thing or people from the place one to the othe place. Along with the times, transportation also develops. The one of transportation that developing is electric bike (e-bike). The development of electric bike is to improve the previous product, so that the electric bicycle that will produced is better than before as models, colors etc. when we make the electric bike design, the first thing that we do is ergonomic analytical so the product that will produced didn’t give long term effect as muscle injury and joint pain for the user. We use analitycal RULA for analytical ergonomi to our design electric bike. We take 31 samples use the database from Student of Industrial Engineering Adi Buana Surabaya College. The result of the RULA value which shows the most ergonomics is at a headtube angle of 15 ° with a RULA value of 3. This shows that the design of this electric bicycle is quite ergonomic and the design is acceptable, although to be ideal in its body posture, further analysis is needed in order to obtain a better RULA value